The prospects of the Russian-Turkish Relations Analytical study (قضايا سياسية, 2022)
The Russian-Turkish relations are complex and enigmatic in their strategic aspects. It has been dominated by pragmatism in all its spheres. These relations have spanned over centuries and they are deeply intertwined. Each country has its own policies that aim to achieve and affect the other country. Each country has international ambitions conflicted with the ambitions of the other. Each country intends to establish its ties with the other for a different set of reasons. However, there are overlapped geostrategic arenas and determinants that represent epicenters of conflict between the two countries. Additionally, international effects and conflicting religious and nationalist grounds that stand against building normal relations between the two countries. However, with the development of the intellectual structure and the advancement of cooperative political and economic traditions, the relations between the two countries will be pushed toward getting integrated under a unifying Eurasian umbrella. Yet, achieving this unity is still far-fetched due to the differences in terms of motives between the two countries.